Reconditioning Load Cell Tensile Testing Machine Capacity 2 Ton - Tarsudin, Tarsudin; Koswara, Engkos; Rachmat, Asep (Jurnal Mekanika dan Manufaktur, 2022)
Test equipment is an educational laboratory facility that is very important in supporting and supporting the teaching and learning process in the laboratory. , load cell is an electronic device that is used as an additional device in a tensile testing machine. The tensile test results will be better or more accurate if the tensile test equipment is equipped with a load cell using a data device system. Obtained from this test, namely the stress value that occurs in the load cell, the stress on the ST37 steel specimen is 48.56 kg/mm², the maximum stress is 952.99 kg/mm². While the stress on the 6061 aluminum specimen is 15.6 kg/mm², and the maximum stress is 306.15 kg/mm². In addition to the workpiece that breaks due to tension, a tensile test curve is also generated. This curve is a description of the workpiece loading process from the beginning of the withdrawal to the end of the workpiece.